High food prices in urban Cameroon: coping strategies and suggested policy actions. Issue 8 (17th November 2017) - Legwegoh, Alexander F.; Fraser, Evan D.G.
ABSTRACT: Governments tend to focus on short-term policies to address the immediate effects of high food prices when spikes occur, while in the long term, urban residents are left to their own devices struggling to ensure adequate household food consumption. Using data collected in three cities in Cameroon among 300 households, this article documents participants' opinions on appropriate policies to address high food prices as well as how households cope with chronic high food prices. It emphasises the importance of long-term government strategies such as improved farm-to-market roads and agricultural sector supports as means to improve food security.